Agriculture, food security, and nutrition in Malawi: Leveraging the links - Aberman, Noora-Lisa; Meerman, Janice; Benson, Todd (International Food Policy Research Institute, 2018)
Although the Malawian food supply is shaped largely by trends in smallholder food crop production, Ma-lawi’s decades-long focus on improving smallholder productivity has only moderately improved food secu-rity and nutrition outcomes. Country statistics indicate an estimated 36.7 percent of rural Malawian house-holds failed to access sufficient calories between 2010 and 2011. During the same period, 47 percent of children under the age of five years were esti-mated to be stunted in their growth. These indicators imply that some Malawian diets are lacking in terms of quantity (total calories consumed), and most are lacking in terms of quality (sufficient calories derived from nutrient-dense foods, such as meat, fish, eggs, dairy, legumes, fruits, and vegetables). Good nutrition requires both enough total calories (quantity) and enough vitamins and minerals per calorie (quality). How can Malawi better leverage its smallholder agriculture sector to improve nutrition? This report provides a series of primary and secondary data anal-yses that examine different aspects of this question.